Pharmacological modulation of the gut-brain axis: psychobiotics in focus for depression therapy - Zainal Abidin, Zakirah; Hein, Zaw Myo; Che Mohd Nassir, Che Mohd Nasril; Shari, Norshafarina; Che Ramli, Muhammad Danial (Frontiers in Pharmacology, 2025)
Major depressive disorder (MDD) is a multifactorial condition shaped by neurobiological, psychological, and environmental influences. Recent evidence highlights the gut–brain axis (GBA), a bidirectional communication system linking the gastrointestinal tract and central nervous system, as an important contributor to MDD pathogenesis via microbiota-mediated mechanisms. This narrative review synthesizes findings from preclinical and clinical studies published in the last decade, with emphasis on mechanistic insights from animal models and translational data from human cohorts. Key pathways include the microbial regulation of neurotransmitter production, immune modulation, vagus nerve signalling, and the metabolism of short-chain fatty acids (SCFAs). Dysbiosis in MDD is frequently characterized by reductions in butyrate-producing genera and elevations in pro-inflammatory taxa which have been linked to neuroinflammation, impaired neurotransmitter synthesis, and hypothalamic-pituitary-adrenal (HPA) axis dysregulation. Interventions such as probiotics, prebiotics, synbiotics, and psychobiotics show promise in alleviating depressive symptoms by modulating the gut microbiota. Emerging evidence also supports the beneficial roles of postbiotics, non-viable microbial products with immunomodulatory and neuroactive potential. Overall, microbial modulation offers a novel adjunctive strategy for depression management, particularly in treatment-resistant cases or to reduce the side effects of conventional drugs. However, heterogeneity in study design, small sample sizes, and limited causal evidence underscore the need for rigorous, large-scale trials. Future directions should prioritize identification of microbial biomarkers, optimization of strain-specific and dose–response data, and integration of gut-targeted approaches into personalized mental healthcare.